Stabilization of sand with colloidal nano-silica hydrosols - O'Kelly, Brendan C. (My University, 2020)
Colloidal nano-silica (NS) hydrosols are electrochemically stabilized, polymerized amorphous silica in low viscosity solutions, and in the form of hydrated gels, silica globules or pellicles.Compared to applications in concrete technology, the use of silica-based binders for ground work applications has received little attention. Silica-based hydrosols impose no known direct risks to humans and are generally courteous to the soil health and ecosystem service functions. Their localizedimpact on microorganisms however needs to be further investigated. To this end, NS hydrosols havea scope for use as an alternative low-viscose material in groundworks. The current understanding ofinteractions between NS hydrosols and soil (sand) is, however, confused by the limited availability ofexperimental evidence concerning undrained static flow and large strain behavior. The contributions,presented in this paper, advance the knowledge through experimental testing, molecular modelling,and micro-analytical measurements. Four grades of colloidal NS (1–15 wt.%) were synthesized forgrouting medium-dense sub-angular fine siliceous sand specimens. Consolidated-undrained triaxial compression testing was performed on the base and treated sand for isotropic consolidation over the effective stress range 100–400 kPa. Overall, silica impregnation produced improvements in yield and residual undrained shear strengths, restricted unwelcomed impacts of excess pore water pressure,and led to the formation of generally more dilative, strain-hardening behavior. Steady states and static flow potential indices are also studied as functions of confinement level and viscosity of the NS grout.
PUBLISHED
Part of the Special Issue ?Toward Sustainable Engineering Structures for Better Safety in Built-Environment?
Keywords: Compensation grouting; Flow; Nano-silica; Sand; Steady-state; Undrained compression; Nanoscience & Materials; Smart & Sustainable Planet; COLLOIDAL SILICA; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; Ground improvement; SILICA; SOIL; SOIL MODIFICATION; Soil Mechanics; Soil Mechanics & Foundations; geotechnical; grouting